(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article considers effective methods of working with explanatory dictionaries in teaching foreign languages on the example of Turkish. Dictionaries are one of the main teaching tools in teaching a foreign language, allowing students to learn new words, understand their meanings and use them in context. In the process of learning Turkish, using explanatory dictionaries, students can not only translate the meaning of a word, but also learn its synonyms, antonyms, places of use and phraseological expressions. The article analyzes the theoretical foundations and methodological methods of working with explanatory dictionaries, and discusses the most effective methods used in teaching dictionaries in Turkish.